2022
DOI: 10.1111/csp2.12690
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of canopy samples to assessments of forestry effects on native bees

Abstract: Forest management is often practiced to enhance conditions for wildlife, including native bees. Evaluations of the effects of forest management on bees have shown that abundance and diversity are higher in newly created earlysuccessional conditions. To date, studies have restricted sampling to the forest understory; however, recent research finds that bee abundance is as high or higher in forest canopies than in understories, suggesting that previous observations of substantially greater bee abundance and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…Our study is the first to demonstrate that bees occupy the aerosphere immediately above the forest canopy; furthermore, the community above the canopy was compositionally distinct with similar abundances compared to lower strata (understory, midstory, canopy). These findings expand our understanding of forest bee communities and build on earlier research that revealed differences between understory and canopy bees (Cunningham-Minnick & Crist, 2020;Milam et al, 2022;Ulyshen et al, 2010;Urban-Mead et al, 2021). However, when attempting to characterize the forest bee community, the importance of sampling the canopy-aerosphere interface hinges upon the question of whether these bees should be considered as part of the forest community, or if they are transients moving among resources.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Our study is the first to demonstrate that bees occupy the aerosphere immediately above the forest canopy; furthermore, the community above the canopy was compositionally distinct with similar abundances compared to lower strata (understory, midstory, canopy). These findings expand our understanding of forest bee communities and build on earlier research that revealed differences between understory and canopy bees (Cunningham-Minnick & Crist, 2020;Milam et al, 2022;Ulyshen et al, 2010;Urban-Mead et al, 2021). However, when attempting to characterize the forest bee community, the importance of sampling the canopy-aerosphere interface hinges upon the question of whether these bees should be considered as part of the forest community, or if they are transients moving among resources.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, studies that quantify potential nesting substrates for wood-nesting bees within the canopy, including those that nest in 'soft' wood, are clearly needed to resolve these discrepancies (Harmon-Threatt, 2020). Milam et al (2022) found that the inclusion of canopy sampling in addition to understory sampling did not influence their ability to characterize the forest bee community. Our study supports their conclusion when only considering bees below the maximum height of the canopy (i.e., understory, midstory, and canopy strata), but further demonstrates that the bee community above the canopy is distinct from lower strata.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations